Analysis of Factors that Influence Fishermen's Production Results in Prigi Nusantara Fishery Port (Ppn) Watulimo District, Trenggalek District - Pratama, Shila Ardy; Setiawati, Ririt Iriani Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of the economic sectors that contributes to the development of the national economy is the marine and fisheries sector. The fishing industry plays a bigger role during economic downturns, particularly when it comes to earning foreign exchange. Meanwhile, the aim of this research is to find out whether there is an influence of production capital on Product of the fishermen in the Trenggalek Regency's Prigi Village, Watulimo District Secondly, to determine if labor has an impact on the productivity of fishermen in Trenggalek Regency's Prigi Village, Watulimo District. The type of research used is a quantitative descriptive approach, basically emphasizing the statistical processing of data analysis in the form of numerical values. It is clear from the multiple linear regression analysis results that the capital value is 33,939, meaning it shows the direction of a positive or unidirectional relationship between capital and production results. The labor value of Labor -4210,909 shows a negative or unidirectional relationship with production results. Meanwhile, There is a duration of -132,287, indicating a negative or unidirectional relationship with production results.